Downhole corrosion behavior of NiW coated carbon steel in spent acid & formation water and its application in full-scale tubing. (August 2016) - Fu, A.Q.; Feng, Y.R.; Cai, R.; Yuan, J.T.; Yin, C.X.; Yang, D.M.; Long, Y.; Bai, Z.Q.
Abstract: Downhole corrosion behavior of NiW coated carbon steel tubing was investigated in spent acid (dilute HCl) solution and formation water by using autoclave and electrochemical techniques, in which dilute HCl with different pH is used to simulate the spent acid during flowback in acidizing process before well production, and the formation water is used to simulate the fluid during well production. Weight loss test in autoclave and electrochemical measurement indicated that NiW coated carbon steel exhibited higher corrosion resistance than carbon steel in spent acid and formation water, especially in spent acid with low pH and formation water at high temperature. According to weight loss test, corrosion rate ratio of carbon steel and NiW coated carbon steel in spent acid with pH = 1, pH = 2, and pH = 4 is 13.7, 14.5, and 6.9, respectively, while corrosion rate ratio of carbon steel and NiW coated carbon steel in formation water at 30 °C, 60 °C, and 90 °C is 85.5, 73.5, and 125.9, respectively. Moreover, the sealing performance of full-scale NiW coated carbon steel tubing was evaluated by using make-and-break test, hydraulic bursting test, and extreme downhole condition corrosion test. No sticky thread was found after 4 times of make up and three times of break out by using maximum recommended makeup torque of 4258 lbf ft, no leakage was detected after hydraulic bursting test at 95.0 MPa for 30 min, and it is observed very slight corrosion on the tubing shoulder experienced make-and-break test under extreme downhole condition. Graphical abstract: Highlights: Corrosion rate ratio of carbon steel and Ni-W coated carbon steel in spent acid with pH = 1, pH = 2, and pH = 4 is 13.7, 14.5, and 6.9, respectively; Corrosion rate ratio of carbon steel and Ni-W coated carbon steel in formation water at 30°C, 60°C, and 90°C is 85.5, 73.5, and 125.9, respectively; No sticky thread was found after 4 times of make up and three times of break out by using maximum recommended makeup torque of 4258 lbf·ft; No leakage was detected after hydraulic bursting test at 95.0 MPa for 30 mins.